Balancing climate goals and biodiversity protection: legal implications of the 30x30 target for land-based carbon removal - Günther, Philipp; Ekardt, Felix (Frontiers in Climate, 2023)
This article examines the legal conflicts between land-based carbon dioxide removal (CDR) strategies and the establishment of protected areas through the lens of international environmental law. We argue that the 2022 Global Biodiversity Framework’s “30x30” target – which aims to protect 30% of global terrestrial and marine areas by 2030 – constitutes a “subsequent agreement” under international law and thus clarifies the legal scope and content of the obligation to establish protected areas under Article 8 of the Convention of Biological Diversity (CBD). Since states have pledged 120 million square kilometers for land-based CDR, these commitments potentially conflict with the “30x30” target, especially if global cropland for food production is to be maintained. Consequently, some land-based CDR strategies may directly or indirectly impede the achievement of the “30x30” target, which could be deemed inconsistent with international law. However, as all international environmental law operates in a continuum, this does not imply that land-based CDR should be categorically ruled out. Rather, states should focus on emission reductions and implementing CDR options that provide the most co-benefits to climate mitigation and biodiversity protection efforts.